Carbonates from Palouse loess at site CLY-2, eastern Washington, USA - Nicholas E Bader; Elliot A Broze; Molly A Coates; McKenzie M Elliott; Gabriella E McGann; Sarah Strozyk; Russell F Burmester (PANGAEA, 2024)
These data are from samples gathered in 2016 from the CLY-2 site in eastern Washington, USA (Location: 46.3131, -118.4874, WGS84). The CLY-2 is a roadcut exposing a vertical face of the Palouse loess containing carbonate paleosol horizons and tephras. The samples were collected from a set of three stepped trenches into the roadcut about 10-20 m apart. Each trench was excavated to a depth of about a meter to expose a fresh surface; the final ~10 cm was excavated with non-ferrous digging tools. Samples were analyzed for organic and inorganic carbon concentrations using an ECS 4010 Elemental Combustion Analyzer CNS (Costech Analytical Technologies, Valencia, CA) at the Arizona Laboratory for Emerging Contaminants. Each sample was ground in a Spex mill with tungsten carbide grind surfaces, then split into two aliquots; one aliquot was run to obtain total carbon, and the second was pretreated stepwise with HCl to remove inorganic C (Nelson and Sommers, 1996, doi:10.2136/sssabookser5.3.c34) before being run to obtain organic C. The difference between these aliquots is the reported inorganic C concentration. We assume all inorganic carbon is calcium carbonate, so CaCO3 is inorganic C multiplied by 8.3 to account for stoichiometric Ca and O.